BARKER, C. & D. GALASINSKI. Cultural Studies and Discourse Analysis : a dialogue on language and identity. London: Sage Publications , 2005. 185p. - Bonfim, João Bosco Bezerra (Cadernos de Linguagem e Sociedade, 2010)
BARKER, C. & D. GALASINSKI. Cultural Studies and Discourse Analysis : a dialogue on language and identity. London: Sage Publications , 2005. 185p.